Gallic acid alleviates hippocampus and cerebellum injuries in a rat model of hepatic encephalopathy - Leila Jafaripour; Hassan Ahmadvand; Esmaeel Babaeenezhad; Khadijeh Esmaeilpour; Marzieh Maneshian; Hamideh Bashiri; Majid Asadi-Shekaari (Scientific Reports)
Abstract Liver cirrhosis leads to portal hypertension and hepatic encephalopathy (HE). Bile duct ligation (BDL) is a valid model for developing HE in animal models. The present study investigated the protective effects of gallic acid (GA) against BDL-induced injuries in male rats. 64 male Wistar rats were randomly divided into eight equal groups: Sham, BDL, BDL+20 mg/kg GA, BDL+30 mg/kg GA, Sham+compound C (CC), BDL+CC, BDL+20 mg/kg GA+CC, and BDL+30 mg/kg GA+CC. The rats received GA by gavage and 6.2 µg of CC via bilateral intraventricular injection daily for four weeks. Serum ammonia, the expression of inflammatory cytokines and caspase-3 (Casp-3), and the number of degenerated neurons were significantly increased in BDL groups compared to the sham group. Antioxidant activity and adenosine monophosphate-activated protein kinase (AMPK) gene expression in the BDL groups significantly decreased compared to the sham group. GA significantly reduced serum ammonia, the expression of inflammatory cytokines, and Casp-3, as well as the number of degenerated neurons in the treated groups. GA significantly increased antioxidant activity and AMPK expression. In the groups that received CC, the improving effect of GA was reduced. GA could protect the hippocampus and cerebellum of male rats against the detrimental effects of BDL due to its antioxidant and anti-inflammatory properties and the activation of AMPK.